A Novel F-Pad for Handwriting Force Information Acquisition - Luo, Jian-Fei; Wu, Bao-Yuan; Lin, Qiu-Shi; Shen, Fei; Wu, Zhong-Cheng (Intelligent Computing Theories and Applications, 2012)
This paper presents a novel pad for handwriting force information acquisition. The pad named F-Pad (force-pad) is capable of capturing both the dynamic handwriting information and the static trajectory of the writing pen. With the core part of the multi-dimension force/torque sensor, the F-Pad can capture the 3-D forces and 2-D torques directly. And with the specially designed structure, other dynamic and static information such as the velocities, accelerations, handwriting shape and slants can be got indirectly. Ordinary pens can be used to write on the pad and the pad provides a real-time visual feedback to gain a natural writing feeling. Basic experiments in which characters are written demonstrate the possibility of handwriting force information detection.